2022
DOI: 10.4018/978-1-6684-3657-8.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Workforce Diversity on Innovation

Abstract: The objective of this chapter is to reveal the impact of workforce diversity on the innovation level of Lebanese family firms. Data for this research work was collected from different Lebanese sectors during the first quarter of 2021. Based on sample of 647 Lebanese family firms, the results of SEM model show that gender diversity has a positive impact marketing, organizational, and product innovation. In addition, the results indicate that the presence of youth in family firms enhances both marketing and proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…For the final objective of the study, result indicated that there was a positive and significant connection between ethnic diversity and contextual performance in selected universities in southwest Nigeria with (r=0.959, p-value<0.05). This result aligns with the positon of Chaarani et al, (2022) which provided that organisations that value diversity are better positioned to understand and serve a broad consumer base. Findings emanating from this study also corroborated the submission of Iffat et al (2021) which exposed that having employees of diverse ethnics enables businesses to better understand the needs and preferences of various target audiences.…”
Section: Discussion Of Findingssupporting
confidence: 76%
See 2 more Smart Citations
“…For the final objective of the study, result indicated that there was a positive and significant connection between ethnic diversity and contextual performance in selected universities in southwest Nigeria with (r=0.959, p-value<0.05). This result aligns with the positon of Chaarani et al, (2022) which provided that organisations that value diversity are better positioned to understand and serve a broad consumer base. Findings emanating from this study also corroborated the submission of Iffat et al (2021) which exposed that having employees of diverse ethnics enables businesses to better understand the needs and preferences of various target audiences.…”
Section: Discussion Of Findingssupporting
confidence: 76%
“…However, while diversity is celebrated for its potential to bring together individuals with varying backgrounds, experiences, and perspectives, it also poses certain challenges that can impact organisational performance via the infusion of certain performance metrics (Onwuzu & Nnamani, 2023). The primary issue lies in understanding how diversity-related factors, such as cultural differences, gender, age, and other dimensions of diversity, can either enhance or hinder an organisation's ability to achieve its strategic goals, foster inclusivity, and maximise overall performance (Chaarani et al, 2022). It is imperative to investigate these challenges to develop effective strategies and best practices that can harness the benefits of diversity while mitigating its potential adverse effects on organisational performance.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation